2007
DOI: 10.1007/s10228-007-0398-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography of bagrid catfishes in Taiwan

Abstract: A phylogeographic analysis of two bagrid catfi shes in Taiwan was conducted using sequence data from a portion of the mitochondrial DNA (mtDNA) control region. For Pseudobagrus brevianalis, which is most probably endemic to Taiwan, a total of eight haplotypes were detected in 189 specimens from nine river systems covering its entire distribution range, from northern to central western areas of the island. Obvious genetic differentiation was observed among its populations (average F ST = 0.753); in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Similar phenomena were also found in the phylogeographic studies of many other freshwater fishes and other organisms in the drainages of Taiwan or on both sides of the Taiwan Strait (e.g. Wang et al, 2004;Watanabe et al, 2007). The transgression of the South China Sea during several inter-ice ages might have led to the colonization and divergence of some fishes or fish populations in the coastal rivers and streams of South China.…”
Section: Introductionsupporting
confidence: 72%
“…Similar phenomena were also found in the phylogeographic studies of many other freshwater fishes and other organisms in the drainages of Taiwan or on both sides of the Taiwan Strait (e.g. Wang et al, 2004;Watanabe et al, 2007). The transgression of the South China Sea during several inter-ice ages might have led to the colonization and divergence of some fishes or fish populations in the coastal rivers and streams of South China.…”
Section: Introductionsupporting
confidence: 72%
“…This species was considered as a valid subspecies of P. brevianalis (sense Chen and Fang, 1999). Althought Ferraris (2007) considered this species to be valid at the species level, Watanabe et al (2007) argued that there was no evidence for the validity of the present species. Regan, 1908b:360 Syntype: BMNH 1909, Lake Candidius, Formosa, coll.…”
Section: Bagridae (159)mentioning
confidence: 80%
“…This pattern of phylogeographic outliers suggests that these populations show a history of isolation from the populations in southern Taiwan and present a relatively high conservation value. In previous studies, two topological barriers, the Miaoli Plateau and Formosa Bank, have been found to represent significant barriers to gene flow in species from various taxa in western Taiwan, such as bagrid catfishes [92] , cyprinids [18] , [23] , [93] , frogs [20] , [22] , [94] , snakes [87] , [88] , and squirrels [89] . Despite the previously reported evidence of amphibian species divergence being caused by a combination of topological barriers and river systems, as for B. robusta [20] , such effects are not detected in B. bankorensis populations.…”
Section: Discussionmentioning
confidence: 99%